Factors Affecting Indonesian Seaweed Exports - Berton E. L. Tobing; Indrawaty Sitepu; Melvi Restina Sitorus; Yona O. Purba (Citakonsultindo, 2024)
This research aims to analyze factors affecting Indonesian seaweed exports in ten destination countries Exports for the 2012-2021 period. Data analysis is multiple linear regression. The data was processed using the MS computer program. Excel, SPSS with multiple linear regression analysis. Simultaneously, the variable volume of Indonesian seaweed exports in the previous year, value Seaweed exports in the export destination country, real GDP per capita in the export destination country and the real exchange rate of the export destination country have a significant effect. Partially, in the variable volume of Indonesian seaweed exports in the previous year, the value of seaweed exports in export destination countries was significant, while the real GDP per capita variables of export destination countries and the real exchange rate of export destination countries were not significant.